Population pharmacokinetics analysis of AMG 416, an allosteric activator of the calcium-sensing receptor, in subjects with secondary hyperparathyroidism receiving hemodialysis - Chen, Ping; Melhem, Murad; Xiao, Jim; Kuchimanchi, Mita; Perez Ruixo, Juan Jose (Journal of clinical pharmacology, 2015)
This study characterizes the population pharmacokinetics of AMG 416, an allosteric activator of the calcium-sensing receptor, in subjects with secondary hyperparathyroidism receiving hemodialysis. AMG 416 doses ranging from 2.5 to 60 mg were administered intravenously as single or multiple thrice weekly (TIW) doses at the end of hemodialysis during rinseback. The influence of demographics, concomitant medications, and other disease-related biomarkers on pharmacokinetic parameters was explored. The predictability of the final model was evaluated using bootstrapping and visual predictive checks. A 3-compartment linear pharmacokinetic model that accounts for the hemodialysis clearance best described the data. Plasma clearance (interindividual variability) was 0.564 L/h (14.0%CV). The hemodialysis clearance was 22.2 L/h. The volume of distribution at steady-state was approximately 624 L (82%CV). The mean time to achieve 90% steady-state predialysis concentrations with 3- and 6-hour hemodialysis TIW was 46 and 32 days, respectively. No statistically significant (P < .01) covariates effect was found on pharmacokinetic parameters. Bootstrapping and predictive checks supported model predictive ability. AMG 416 exhibits linear and stationary pharmacokinetics within the range of doses evaluated. Within the range of covariate values investigated, pharmacokinetically driven adjustments of AMG 416 dosing on the basis of these covariates were not warranted.